'Wow, it's at the University'! Experiences of people with mental illness of an educational arts programme. (1st December 2019) - Lambley, Ruth; Kaley, Elizabeth; Morris, Rebecca; Robinson, Anna; Rowe, Nick; Sellar-Edmunds, Jean; Wynn-Werninck, Tim; Anderson, Emma
AbstractThis study gathered the experiences and perceptions of participants of a university-based programme of free arts education for people who use mental health services, known as Converge. A total of 70 per cent of the authors have lived experience of mental health difficulties and attend Converge courses. A Participatory Action Research (PAR) approach was taken, using Photo Elicitation to facilitate interviews with relatively new Converge participants. An inductive thematic analysis of the data identified four themes: establishing community; purpose; student not patient; and accessing valued, inclusive spaces. These reflected findings in the existing literature about the mental health benefits of the arts and factors important to the process of recovery. A major finding was the clear indication that locating courses in socially valued and inclusive venues is of very high importance to participants, and that this seems to amplify benefits they experience from attending. This suggests that forming partnerships between socially valued spaces and mental health services is worth energetically pursuing.